COMPACT DIRECTIONAL COUPLERS USING COMBINATION OF MICROSTRIP AND SLOT LINES - Romanenko, S. N.; Dmitrenko, V. P.; Tverdenko, A. V. (Radio Electronics, Computer Science, Control, 2019)
Context. Transition of modern electronics to higher frequencies is directly related with an extremely important problem of miniaturization of microwave integrated circuits. Conventional planar structures such as microstrip directional couplers have the feature – their linear dimensions are defined by the wavelength in the transmission lines, so the use of such structures for miniaturization of microwave integrated circuits becomes problematic. Objective. Using 3D-structures on combinations of transmission lines to study frequency properties of two possible implementations of quarter-wave directional couplers based on a combination of microstrip and slot transmission lines. Obtaining simple analytical expressions for calculating the electrophysical parameters of these directional couplers and confirm their properties by rigorous electrodynamic calculation. Methods. An even-odd mode decomposition technique and the scattering matrix theory were used to derive simple analytical formulas for calculating impedances of transmission line segments that define the topology of couplers considered. Results. Electrodynamic modeling of proposed couplers with dispersion and losses in the lines showed that the proposed constructions have better frequency characteristics in comparison with traditional three-branch microstrip directional couplers. It is also shown that the considered designs of couplers have great potential in the selection of the desired electrical characteristics of devices. Conclusions. The presented compact couplers can find a broad range of applications in mobile communication systems for decoupling of channels, division of power and frequency conversion. The method of transition from planar to three-dimensional structures used in the development of directional couplers on combinations of transmission lines permits not only to create compact devices with desired characteristics but also paves the way for significant decrease in the size and costs of the broad range of electronic equipment utilizing such couplers.